Acompanhamento farmacoterapêutico de pacientes transplantados renais : da descrição aos desfechos clínicos - Martins, Bruna Cristina Cardoso (2015)
Renal transplanted patients have a c omplex pharmacotherapy, being possible for pharmacists to contribute with the pharmacotherapy and its benefits management by integrating the multiprofessional team. This work aimed to assess the pharmacotherapeutic follow - up of renal transplanted patients considering the clinic outcome after the interventions performed by the pharmacist. It is a descriptive study with quantitative, exploratory and retrospective approach carried out in the Renal Transplant Service Ambulatory from a University Hospital (Fortaleza/Ceará), during the period from January to December 2013. Were included registers from patients who had at least two appointments in the Pharmaceutical Care Service during the stu dy period. The Drug Related Problems (DRP), Pharmaceutical Interventions (PI) and Clinic Outcomes were categorized through a classification used by the Clinical Pharmacy Service of the institution. The Negative Outcomes associated with Medication (NOM) wer e classified accordingly to the Third Granada Consensus. The impact and significance evaluation of the PI was made using the Farré Riba method. The Pharmacotherapy Complexity Index (PCI) assessed the pharmaceutical form, intake frequency and additional ins tructions. During the period 237 patients were attended by the pharmacist, with 109 from them attending the inclusion criteria of this study. Their profile was: 1.4% (n = 56) men; 35% (n = 38) Basic disease of unknown etiology; mean age of 44.9 years (± 10 .8) and most with education level "elementary school". The average number of drugs prescribed was 8.5 (± 2.6) in the 1st consultation and 8.0 (± 2.4) at the last. The average total points of PCI was 46 (± 13.7) in the 1st query and 43.7 (± 12.3) in the las t one (p <0.05), the minimum score of 19 was associated with the use of 3 medicines and the maximum of 83.5 points to 16 medicines. It was observed that patients with up to 180 days after transplantation showed higher scores on PCI (p <0.05) with predomina nce of the capsule / tablet formulation in the pharmacotherapy, 1 per day and 12/12 hours dosage and ̳take as directed‘, ̳take on specific times‘ and ̳interaction with food‘ additional instructions. 113 NOM were identified with the most frequent being "unt reated health problem" (61.9%; n = 70). 467 PI were held, with predominance of the one referring to "educate about the use of the drug" (77.5%; n = 362). With the completion of the IF, 86% (n = 97) of risk to or worsening of the health problems related to the drug were prevented and 8.8% (n = 10) had clinical improvement (p <0.05) with the latter classified as "extremely significant" because they generated a very significant increase in the effectiveness of therapy (p <0.05). The findings of the study show that renal transplanted patients under pharmacotherapeutic follow - up, despite the complexity of pharmacotherapy identified, have had negative outcomes avoided and minimized as well as improvement of health problems associated with the pharmacotherapy of tr ansplantation after completion of the pharmaceutical interventions